2017
DOI: 10.3928/01484834-20170712-06
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Flipped Learning of a Nursing Informatics Course

Abstract: A flipped learning nursing informatics course is an effective teaching strategy for preparing new graduate nurses in the clinical setting. [J Nurs Educ. 2017;56(8):477-483.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 21 publications
0
17
0
1
Order By: Relevance
“…In this study, during the offline classes that corresponded with the in‐class times, the students were provided adequate time to debate a topic with each other and the educator. Flipped learning classes using film clips have been found to help learning and promote interaction among teachers, students, and peers (Oh, Kim, Kim, & Vasuki, ). The integration of online into offline classes or courses can help educators to expand their teaching beyond distributing course content to in addition facilitating or assessing learning outcomes and achievement.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, during the offline classes that corresponded with the in‐class times, the students were provided adequate time to debate a topic with each other and the educator. Flipped learning classes using film clips have been found to help learning and promote interaction among teachers, students, and peers (Oh, Kim, Kim, & Vasuki, ). The integration of online into offline classes or courses can help educators to expand their teaching beyond distributing course content to in addition facilitating or assessing learning outcomes and achievement.…”
Section: Discussionmentioning
confidence: 99%
“…Background/rationale: Contemporary nursing education aims to prioritize student-centred learning, which is perceived as high ordered, flexible, and individualized [1]. Recent technology advancements have accelerated education innovations such as blended learning by providing easy access to information [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…In FC, teachers use technology and share pre-class learning material to activate lowordered learning, and students study the material before attending the F2F classroom. Teachers design the F2F classroom as an interactive educational environment by using student-centred teaching strategies for allowing the students to apply or evaluate the learnt concepts [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flipped Learning has been applied in some courses of university education such as English, informatics, and specific subjects of medicine and nursing among others (Heeseung et al, 2015;Noor-Akmal, 2016;O'Connor et al, 2016;Oh, Kim, Kim, & Vasuki, 2017;Pence, 2016). In these studies, advantages found when FL was applied were more engagement in the course, self-regulation and more motivation in comparison with regular classes.…”
Section: Introductionmentioning
confidence: 99%